Runner's world : (Wiley Publíhing, Inc., 1978)
Join 200,000 other runners in using the bestselling training diary from the world's leading running magazine! Runner's World Training Diary Even if you've read Bill Rogers, George Sheehan, or Jim Fixx and have benefited from the advice of running experts, you can gain even more knowledge by keeping and studying your own personal running record. Inside this handy diary, Runner's World provides the outline. You fill in the facts about each day's run, such as your pace, the distance you ran, your pulse rate, and weather conditions. You set the goals--to run every day or twice a week, to log two or ten miles a day, to train for a 10K or a marathon--then note your progress. You discover what really works, and what doesn't. In addition to providing a useful format and generous space for charting an entire year's running, the Runner's World Training Diary also includes: * Charts to record racing results, best times, a year's running at a glance * Tables listing pacing rates, wind-chill readings, metric distance conversions * Warm-up exercises and tables showing the caloric cost of running * Helpful running hints * Pages for training records, schedule planning, and much more!